Pengaruh Kompetensi Guru Dan Metode Pembelajaran Terhadap Hasil Belajar Pada Siswa MTs - Didit Darmawan; Hilya Andini; Pratiwi Fadia Sholihah (Ameena Journal, 2026)
The low learning outcomes of Madrasah Tsanawiyah (MTs) students are often associated with suboptimal teacher competence and the use of learning methods that lack variety, causing students to lack focus, motivation, and active involvement in learning. This study aims to analyse the influence of teacher competence and learning methods on the learning outcomes of Madrasah Tsanawiyah (MTs) students. The research method used is a literature study with a descriptive qualitative approach, which examines various sources such as articles, journals, and related scientific literature. The results of the study show that both variables have a significant and interrelated influence on improving student learning outcomes. Teacher competence, which includes pedagogical, professional, social, and personality aspects, is the main foundation for creating effective learning. Meanwhile, the selection of appropriate and innovative teaching methods such as inquiry learning, active learning, mind mapping, outdoor learning, and game-based learning has been proven to increase student motivation, engagement, and understanding. The implications of this study emphasise the importance of developing teacher competence and applying varied teaching methods to create a productive and enjoyable learning atmosphere, thereby optimising MTs students' learning outcomes holistically.